VICISSITUDES AND FRAGILITIES IN THE PSYCHOLOGICAL NOVEL: THE CREATIVE PROCESS OF MENALTON BRAFF - Costa e Silva, Natali Fabiana (Revista da Anpoll, 2016)
Menalton Braff is a Brazilian writer. Since his debut in 1984, he published more than 20 books, he won the Jabuti Award in 2000 and almost every year he is a finalist or semi-finalist in major Brazilian literary awards. This article aims to study the author’s creative process, which ranges from an engaged literature to the increase of subjectivity through the stream of consciousness. It is possible to capture how his narrative is built up on the dialogue between form and content as well as how he engages aesthetic and ethic project. This work is licensed under a Creative Commons Attribution 3.0 License.